PEMILU DAN KONSTITUSIOLITAS SISTEM NOKEN - Muhammad Fauzan Azim (Turast: Jurnal Penelitian dan Pengabdian, 2013)
The principle “asas luber jurdil”—one man, one vote, one value as its character—is frame of the generalelection system applicated in general election of Indonesia. This principle is to protect the popular sovereigntythrough the voting right independently. The implementation of popular sovereignty in the general election ismanifestation of majority aspiration as the main principle of democracy. On other hand, in Indonesia can befound the unique system in implementing the popular sovereignty. It is named noken system—with MK’s actNomber 47-81/PHPU.A-VI/2009. The research aims to study it as objective of studies. Generally, the researchshown that Noken System has presented the popular sovereignty of indigeneous law of Yohukimo.